Experimental Investigation of Pipeline Emulsions Flow Behaviours - Lim, Jit Sen (Curtin University, 2016)
This research presents the stability and phase inversion of water-oil emulsions formed through flow shear, and the effect on flow pressure drop. Flow pressure drop profile and dissipation energy profile are established to deliberate further on this effect. The flow pressure drop profile is an important optimization tool in the industry to determine the values of flow rate and pump discharge pressure, in mitigating the unwanted formation of emulsions and higher additional pressure loss.